Modeling of single phase off-grid inverter for small standalone system applications - Rodney H.G. Tan; Chong Boon Chuin; Sunil Govinda Solanki (Institute of Advanced Engineering and Science, 2020)
This paper presents the detail circuitry modeling of single phase off-grid inverter for small standalone system applications. The entire model is developed in MATLAB/Simulink platform using circuitry model. This off grid inverter consists of a high frequency DC-DC step up converter cascaded with a full bridge PI control voltage source inverter using SPWM modulation with LC filter to produce sine wave output. This is a common design used in many small commercial off-grid inverter. This off-grid inverter model is capable to produce AC sinewave output voltage at 230 V 50 Hz up to 1 kW power from a 48 V DC lead acid battery source. The AC sine wave output waveform achieved a voltage Total Harmonic Distortion (THD) of less than 1 % which is almost a pure sine wave. The conversion efficiency performance of the off-grid inverter achieved more than 94 %. The performance of the model is validated by real commercial off-grid inverter. The performance validation experiment shows that the off-grid inverter Simulink model conversion efficiency and THD performance are comparable to the commercial off-grid inverter. This model contributes to assist small to medium standalone system load and battery sizing design with greater accuracy.